(p)ppGpp imposes graded transcriptional changes to impair motility and promote antibiotic tolerance in biofilms - Florian Engelhardt; Kathryn Turnbull; Melisa Gür; Mathias Müsken; Matthias Preusse; Susanne Häussler; Mohammad Roghanian (npj Biofilms and Microbiomes)
Abstract (p)ppGpp is the master regulator of bacterial stress responses, orchestrating cellular physiology via the stringent response to promote survival and adaptation. In response to nutritional challenges and stress, (p)ppGpp extensively rewires the transcriptome. Here, we demonstrate that (p)ppGpp production in Pseudomonas aeruginosa is gradual and relative to stress severity, rather than binary (on/off). Transcriptomic analysis reveals that (p)ppGpp ensures proportionate cellular responses to stress by imposing a layer-by-layer regulation of gene expression. These effects intensify as (p)ppGpp levels rise, with up to a quarter of the genome differentially regulated at maximal levels. Initial increases in (p)ppGpp reduce growth and metabolism while suppressing motility and pyocyanin production. At higher levels, biofilm-related genes are upregulated at the expense of virulence genes, promoting the formation of condensed biofilms. Finally, (p)ppGpp-driven reprogramming induces antimicrobial tolerance, particularly under biofilm conditions, independently of its effects on growth.